SPECTRAL STUDIES AND ANTIMICROBIAL SCREENING FOR SOME NOVEL CHALCONES ANALOGUES - KATEB, BUSHRA AHMED; HUSSIEN, ABDULKAREEM ALI; BASEER, M. A. (International Journal of Current Pharmaceutical Research, 2016)
Objective: The present work aim to study the spectral and antimicrobial activity for synthesized chalcones Methods: The synthesized Chalcones were characterized by Physical and spectral methods such as melting point, IR, 1H-NMR and Mass analysis. The synthesized compounds have been screened for their antimicrobial activity. Results: The biological data showed that compounds III, VII had strong activities against the Staphylococcus aureus, Bacillus subtilis, and Pseudomonas aeruginosa, but not activity against fungus. Conclusion: The main purpose to use an easy and useful method to synthesize biologically active chalcone.